O aparelho de linguagem da psicose: montagem de um caso clínico ou considerações sobre uma função de gozo - Renata Damiano Riguini (2008)
In this descriptive study we try to articulate what it is made use on the language in the psychosis e the language device, while joy device. Its objective was to unite other experiences to the clinic, necessarily, to articulate the Fabiano case that, with wisdom, it showed to me the language that is used for him. For in such a way, a bibliographical research was carried through that, at the first moment, it was directed for the question of the language in the psychoanalysis, analyzed from the concept of significant in Lacan. At the second moment, we were stimulated to argue the particularitities of the language in the psychosis, in order to guide the ways and possibilities for where it would pass Fabiano, which made possible in them to carry through a descriptive study, detailed of the language in this study of case. To be continued, following the case, it was presented for us placed the mark of the logic of Frege, precious instrument for Fabiano and, still more valuable in our passage, rank to be the axle that allowed in them to legalize something on the language in the psychosis, in its particularitity, the singularity of the language of Fabiano and to make of this everything a joy, language device and to know.